2019
DOI: 10.1177/1120672119845224
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Rituximab on Graves’orbitopathy: A retrospective study of 14 patients

Abstract: Purpose: Management of Graves’ ophthalmopathy remains challenging. Over the last decade, previous studies have shown promising results for Rituximab in the treatment of Graves’ ophthalmopathy. We present the response of 14 individuals with active moderate-to-severe Graves’ ophthalmopathy to Rituximab, representing one of the largest retrospective case series reported to date. Methods: Rituximab was administered intravenously, 1000 mg twice at a 2-week interval. The primary end point was a clinical activity sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 31 publications
(69 reference statements)
1
24
0
7
Order By: Relevance
“…There has been substantial research into the effects of rituximab in Graves ophthalmopathy therapy, and many clinical trials have demonstrated that rituximab has therapeutic effects, with limited side effects [ 29 ]. As an anti-CD20 monoclonal antibody, rituximab can inhibit B cell activation and decrease inflammatory cytokine secretion [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There has been substantial research into the effects of rituximab in Graves ophthalmopathy therapy, and many clinical trials have demonstrated that rituximab has therapeutic effects, with limited side effects [ 29 ]. As an anti-CD20 monoclonal antibody, rituximab can inhibit B cell activation and decrease inflammatory cytokine secretion [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…There has been substantial research into the effects of rituximab in Graves ophthalmopathy therapy, and many clinical trials have demonstrated that rituximab has therapeutic effects, with limited side effects [ 29 ]. As an anti-CD20 monoclonal antibody, rituximab can inhibit B cell activation and decrease inflammatory cytokine secretion [ 29 ]. As modern therapy strategies for Graves ophthalmopathy are concerned with individualization and precision, immune-based therapies have become increasingly popular, and numerous antibodies have been applied as new therapies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, B cell infiltration was absent in some immunohistochemically analyzed GO orbital tissues [36], and this might explain why some patients failed to respond to RTX. A recent French retrospective series also found limited efficacy of RTX in steroid-refractory active moderate-to-severe GO with long disease duration (median 26 months) [64]. A few patients in the RTX groups of both randomized trials developed a transient increase in proptosis or visual loss, and 2 patients even developed frank DON.…”
Section: Rituximabmentioning
confidence: 99%
“…Furthermore, 14 patients with active and moderate-to-severe GO, of whom 11 CS-refractory, were administered with ivRTX (1000 mg twice with a 2-week interval), reporting that RTX was well-tolerated (49). A modest amelioration of CAS, and disease inactivation in half of the patients, were reported.…”
Section: Therapies For Gomentioning
confidence: 99%